Band structure of LaPO₄ - Syrotyuk, S.V.; Chornodolskyy, Ya.M.; Vistovskyy, V.V.; Voloshinovskii, A.S.; Gektin, A.V. (Functional Materials, 2013)
The calculations of band structure of LaPO₄ crystal of monoclinic and hexagonal lattice symmetry is performed using the PAW formalism and taking into account the strong local correlations in the PBE0 GGA approximation. The obtained results are in good agreement with the experimental ones obtained from the luminescence excitation spectra of intrinsic emission of LaPO₄ crystal. The calculation of the partial electron state density of LaPO₄ crystal is performed and the nature of the various states in the overall density formation is explained.